Development and support of small innovative entrepreneurship in Europe and the USA - Petrunenko, Iaroslav (2020)
Modern business practice shows that small innovative entrepreneurship needs special support in the context of rapid development of science and technology. To implement the outlined, various business support programs are being developed at a rapid pace, which are being actively implemented in practice. The aim of the article is to present the conceptual features of the development and support of small innovative entrepreneurship in Europe and the United States. The purpose of the academic paper is to present the conceptual features of supporting small innovative entrepreneurship in Europe and the United States of America.